Acute safety and performance outcomes from the inspIRE trial using a novel pulsed field ablation system for the treatment of paroxysmal atrial fibrillation. (14th October 2021) - De Potter, T; Reddy, V; Neuzil, P; Rackauskas, G; Anic, A; Grimaldi, M; Di Biase, L; Natale, A
Abstract: Background/Introduction: The inspIRE clinical trial was designed to assess the safety and efficacy of a fully integrated biphasic pulsed field ablation (PFA) system comprised of a multi-channel generator, variable decapolar irrigated loop circular catheter, and mapping system (Figure A) for the treatment of paroxysmal atrial fibrillation (PAF). Purpose: Using this novel PFA system in a multicentre clinical trial, we present the initial feasibility of electrical pulmonary vein isolation (PVI), procedural performance, and acute safety results. Methods: inspIRE is a prospective, non-randomized, multi-centre study, planned to enrol up to 550 patients. PVI is performed with the novel, variable loop circular catheter, compatible mapping system and generator. Acute procedural effectiveness (entrance block in all clinically targeted PVs post adenosine/isoproterenol challenge) and the incidence of primary adverse events (PAEs) were assessed. PAEs are defined as the occurrence of cardiac tamponade/perforation, myocardial infarction, stroke/cerebrovascular accident, thromboembolism, transient ischemic attack, permanent phrenic nerve paralysis, pulmonary edema, pericarditis, and any major vascular access complications within 7 days of the ablation procedure. Additionally, any incidence of procedure or device related death, atrio-esophageal fistula, or PV stenosis (related to the ablation procedure or study catheter) within the 12M follow-up period is classified as a PAE. Results: A total of 35 PAF subjects (age 59.7±10.7 years, 54.3% male) were treated across 5 European sites by 6 operators. Acute procedural success was achieved in 100% of study subjects (Figure B) with zero incidence of PAEs. Mean total procedure time was 82.9±19.9 minutes with 27.0±11.9 minutes of PFA from first to last application. Average fluoroscopy use was 10.6±6.8 minutes and LA dwell time was 45.6±15.3 minutes. Conclusion: Initial results of the inspIRE trial demonstrate the acute safety and effectiveness of the new integrated IRE circular catheter, mapping system and generator for PVI in PAF patients. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): inspIRE is a company-sponsored study funded by Biosense Webster, Inc.